Plan de promoción y publicidad para la cooperativa de ahorro y crédito “Antorcha Lltda.”, del cantón Quinindé, provincia de Esmeraldas, año 2012 - López Villegas, Martha Beatriz (2012)
The plan of promotion and publicity for the cooperative credit unions "Antorcha Ltda." in the canton Quinindé, took place it in order to investigate the partners, to know the level of satisfaction of the products and services offered by the financial institution, an analysis internal and external of the institution, with the aim of establishing fortresses weaknesses, opportunities and threats. The purpose of the study is to develop a proposal for promotion and advertising that allows knowing all the products and services offered by the cooperative in the sector. The research took place in the cooperative credit unions "Antorcha Ltda.", located in the city de Quinindé of Esmeraldas province, used the conceptualizations to sustain the study with the investigation of the framework theoretical, in the part concerning the collection of information is are synthesized responses according to a questionnaire established for this purpose. Various types, methods, techniques and instruments of research, which made it possible for data collection, interpretation and analysis of the same, were used to implement the study. The lack of training in the field of cooperatives has given rise to not appreciate the benefits afforded by the institution, in the same way the limited knowledge of tools of marketing within the cooperative and the lack of an advertising plan has affected clients increased, which is why the recruitment of new members has been affected, despite the fact that the entity has financial backing to serve with credits, potential partners open their accounts of savings in other financial institutions. It is therefore a fundamental requirement that the cooperative redefine their behavior of service to the community Quinindeña, achieving a greater number of partners increased, strengthened to be able to offer a better service to their cooperates, reaching thus the objectives that it has been proposed as a financial institution. The field study showed that there is satisfaction on the partners, especially for services and attention towards them, there is also opening in citizenship for receptive type of promotion you want to design, which is positive for the institution, since this strategy will make it possible to increase its positioning in the market and consequently their competitiveness. Quinindé residents surveyed stated that he would like to cooperative credit unions "AntorchaLtda.", carry out promotions in the savings books, 85% of those questioned indicated positive acceptance of belonging to the institution as an alternative in the use of their services and 81% of respondents expressed the possibility of saving in the cooperative these data were instrumental in the development of the plan of promotion and advertising. The questions revealed important data on the diversification of commodities, which proved the hypothesis, noted that it is essential to have another kind of services for members, 58% of the partners indicated that having an ATM is positive for the growth of the institution, that 33% of those surveyed responded that the promotions would cause them increased interest in products and services offered by savings and credit cooperative "Antorcha Ltda." The FODA found that the shortcomings due to low competitiveness with other institutions, so the plan of promotion and advertising prophets will contribute here, so is necessary manner the confidence and loyalty of partners, genera new financial products to make more attractive to the institution for the market in the town of the Canton in Quinindé and is appropriate and indispensable using the plan of promotion and advertising as a tool practical, agile and modern growth in the local market. The plan will focus on the community of the sector and its surroundings, inform the benefits afforded by the financial institution, as also the strengthen the corporate image, raise advertising strategies, budgets , which include posters, billboards and flyers, trying to capture the attention of public and increase the partners in the entity.